STRATEGI PEMBELAJARAN PENDIDIKAN ANAK USIA DINI DALAM MENDUKUNG PEMBELAJARAN MASA PANDEMI COVID 19 - Sry Anita Rachman (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study is to describe strategies that can be used in early childhood education learning during a pandemic so that activities can run optimally. This study describes things that can be done in learning such as learning activities, collaboration with parents of children, learning methods and strategies applied, as well as media used in teaching and learning activities during a pandemic. This study uses a descriptive method by conducting a survey to 10 teachers in the village of Masbagik Utara Baru. The research was conducted by distributing questionnaires via whatsapp, with the results of the study: teachers have packaged learning in various ways ranging from forms of learning according to needs, paying attention to children's needs, activities that train children's independence, using appropriate media, using various methods, and establishing cooperation with the child's parents.